2016
DOI: 10.1080/19443994.2015.1054315
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of malachite green and crystal violet cationic dyes from aqueous solution using pumice stone as a low-cost adsorbent: kinetic, equilibrium, and thermodynamic studies

Abstract: In this study, the sorption potential of pumice was investigated as geomaterial adsorbent for removal of two cationic dyes, malachite green (MG) and crystal violet (CV), from aqueous solution. In batch experiments, the effects of contact time, particle size, absorbent dose, solution pH, initial dye concentration, and temperature of MG and CV ions on the pumice adsorption capacity was studied. The characterization of the pumice has been accomplished by X-ray fluorescence spectroscopy, scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(16 citation statements)
references
References 50 publications
(69 reference statements)
0
15
0
1
Order By: Relevance
“…In this study, Langmuir, Freundlich, Tamkin, and Dubinin-Radskovich isotherms were used for the adsorption analysis of the dyes. 11,51 The results of this study are presented in Table S4 (ESI †) and Fig. 9.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, Langmuir, Freundlich, Tamkin, and Dubinin-Radskovich isotherms were used for the adsorption analysis of the dyes. 11,51 The results of this study are presented in Table S4 (ESI †) and Fig. 9.…”
Section: Resultsmentioning
confidence: 96%
“…Among the advantages of this process compared to other separation processes are simplicity of operation, insensitivity to toxic substances, and low cost with high efficiency. 11 Nowadays, researchers are focusing more on synthesizing low-cost adsorbents with high adsorption capacity to remove dye contaminants from wastewater. A wide range of materials has been studied to remove dyes, including bentonite, clay, activated carbon, polymers, and wheat bran.…”
Section: Introductionmentioning
confidence: 99%
“…The negative DG indicates the spontaneous nature of the adsorption process of CV onto clay adsorbents, whereas the positive value of DH indicated that the adsorption process was endothermic in nature and positive values of DS indicate an increase the disorder on adsorption surface of solid/solution interphase with the rise in temperature. Crystal violet adsorption process onto red mud activated by acid and pumice stone also showed similar behavior (Shayesteh et al, 2016;Zhang et al, 2014). CV adsorption onto bentonite clay was also endothermic in nature (Eren, 2009).…”
Section: Resultsmentioning
confidence: 72%
“…From the thermodynamic analysis results provided in Figure 9 and Table S4 in the ESI, significant parameters including Δ H °, Δ S °, and Δ G ° were calculated for the adsorption of clenbuterol onto the MIPMs. The positive Δ H ° and Δ S ° values indicate the endothermic nature and randomness of the adsorption of clenbuterol onto the MIPMs [54]. The positive Δ G ° value reveals that the adsorption reaction requires energy.…”
Section: Resultsmentioning
confidence: 99%